Using online multiple choice questions with multiple attempts: A case for self-directed learning among tertiary students - Ng Wen Lee; Wan Noor Farah Wan Shamsuddin; Lim Chia Wei; Muhammad Nur Adilin Mohd Anuardi; Chan Swee Heng; Ain Nadzimah Abdullah (International Journal of Evaluation and Research in Education (IJERE), 2021)
Criticisms on multiple choice questions (MCQs) include the possibility of students answering MCQs correctly by guessing, and MCQs generally are said to fall short in cultivating independent learning skills, such as taking charge of their learning goals. Countering these common concerns, this research used online MCQ exercises with multiple attempts to investigate the experiences that drove students to become self-directed learners. In this research, 60 students completed two sets of online MCQ exercises with multiple attempts outside of classroom time for six weeks consecutively. Both focus group interviews and an online survey were conducted to investigate the experiences of using online MCQ exercise with multiple attempts in relation to the development of self-directed learning (SDL). The findings of the study showed that the criticisms may be unfounded. Data leads to the conclusion that the majority of the students do not just try to guess at the correct answers. Rather, many of them attempted the online MCQ exercises more than once to improve themselves indicating that they were interested in self-learning. Students also reported that they utilised search and inquiry skills that clearly showed motivated initiatives to plan how to overcome their weaknesses by independently looking for relevant resources, determine their own learning goals, and evaluate their own learning performance as a firm indicator of SDL development. Based on the findings, this study is able to refute the claim that MCQs are unable to cultivate independent learning skills.